Hematopoietic Stem Cell Transplantation and Vasculopathy Associated With STAT3-Dominant-Negative Hyper-IgE Syndrome - Ponsford, Mark J.; Clark, James; Mock, Joel; Abinun, Mario; Carne, Emily; El-Shanawany, Tariq; Williams, Paul E.; Choudhury, Anirban; Freeman, Alexandra F.; Gennery, Andrew R.; Jolles, Stephen (Frontiers in Pediatrics, 2020)
Dominant negative mutations in the transcription-factor STAT3 underlie the rare primary immunodeficiency Job’s syndrome. Allogeneic Hematopoietic Stem Cell Transplantation (HSCT) has shown promise in correction of the underlying immunological defect, with one report suggesting HSCT can prevent development of wider connective tissue complications. Here, we report the case of a 26 year old male who developed an acute ST-elevation myocardial infarction due to coronary artery ectasia and thrombosis, occurring despite pediatric allogeneic HSCT for STAT3-HIES and a predicted 10-year conventional cardiovascular risk of 0.1%. Vasculopathy associated with STAT3-HIES may persist or arise following HSCT and can precipitate life-threatening complications. This has implications for counselling and vascular surveillance, and highlights the need for further studies to determine the risk, pathogenesis, and optimal management of the vasculopathy associated with STAT3-HIES.